Hubungan Mutu Pelayanan Kebidanan Dengan Kepuasan Ibu Hamil dalam Mendapatkan Pelayanan Antenatal Care di Puskesmas Muara Ancalong Kabupaten Kutai Timur - Nurlinda, Fitria; Adrianto, Ratno; W, Ratih Wirapuspita. (Syntax Corporation, 2025)
The quality of health services is the level of individual and community health services that can improve optimal health outcomes. The maternal mortality rate in Indonesia is still a big problem, so maternal health services are a top priority in health development. The purpose of this study is to determine the relationship between the quality of midwifery services and the satisfaction of pregnant women receiving antenatal care services. This type of cross-sectional quantitative research was conducted on 95 pregnant women respondents in the Muara Ancalong Health Center area in 2024. Bivariate analysis uses chi-square test, while multivariate analysis uses logistic regression test. The results showed that there was a relationship between the security variable and the satisfaction of pregnant women (p=0.032), there was a relationship between the comfort variable and the satisfaction of pregnant women (p=0.0001), there was a variable relationship of technical competence to the satisfaction of pregnant women (p=0.0001), there was a variable relationship of access/easy access to the satisfaction of pregnant women (p=0.041) and there was a variable relationship of reliability to the satisfaction of pregnant women (p=0.002). The variables that have the greatest relationship with the satisfaction of pregnant women getting antenatal care services are comfort and technical competence. The variables of comfort and technical competence have a strong relationship with the satisfaction of pregnant women in getting antenatal care services, the suggestion of the Puskesmas to give priority to pregnant women regarding their comfort and evaluate needs related to the comfort factor of service recipients and the need to improve the competence of service providers.